Serum Bilirubin Levels and Disease Severity in Patients with Pneumoconiosis - Peng, You-Fan; Deng, Jun-Hua; Huang, Xiao-Ying; Zhang, Qing-Song (Canadian respiratory journal, 2023)
Aim. To investigate the association between serum bilirubin and disease severity in patients with pneumoconiosis. Methods. The study comprised 45 patients with pneumoconiosis retrospectively; all pneumoconiosis patients were classified into I, II, and III stage according to the radiological severity. Results. Serum direct bilirubin levels were significantly lower in III stage pneumoconiosis patients than those in I/II stage (p = 0.012) but not serum indirect bilirubin. Serum direct bilirubin was negatively correlated with radiological severity in patients with pneumoconiosis (r = −0.320; p = 0.032); by multiple linear-regression analysis, we observed that serum direct bilirubin levels had independent association with radiological severity in patients with pneumoconiosis (beta = −0.459; p = 0.005). Conclusions. Serum direct bilirubin levels are negatively associated with disease severity in patients with pneumoconiosis.